Effects of High‐Impact Training on Bone and Articular Cartilage: 12‐Month Randomized Controlled Quantitative MRI Study - Multanen, Juhani; Nieminen, Miika T; Häkkinen, Arja; Kujala, Urho M; Jämsä, Timo; Kautiainen, Hannu; Lammentausta, Eveliina; Ahola, Riikka; Selänne, Harri; Ojala, Risto; Kiviranta, Ilkka; Heinonen, Ari (Journal of bone and mineral research, 2014)
ABSTRACT Osteoarthritis and osteoporosis often coexist in postmenopausal women. The simultaneous effect of bone‐favorable high‐impact training on these diseases is not well understood and is a topic of controversy. We evaluated the effects of high‐impact exercise on bone mineral content (BMC) and the estimated biochemical composition of knee cartilage in postmenopausal women with mild knee osteoarthritis. Eighty women aged 50 to 66 years with mild knee osteoarthritis were randomly assigned to undergo supervised progressive exercise three times a week for 12 months (n = 40) or to a nonintervention control group (n = 40). BMC of the femoral neck, trochanter, and lumbar spine was measured by dual‐energy X‐ray absorptiometry (DXA). The biochemical composition of cartilage was estimated using delayed gadolinium‐enhanced magnetic resonance imaging (MRI) cartilage (dGEMRIC), sensitive to cartilage glycosaminoglycan content, and transverse relaxation time (T2) mapping that is sensitive to the properties of the collagen network. In addition, we evaluated clinically important symptoms and physical performance–related risk factors of falling: cardiorespiratory fitness, dynamic balance, maximal isometric knee extension and flexion forces, and leg power. Thirty‐six trainees and 40 controls completed the study. The mean gain in femoral neck BMC in the exercise group was 0.6% (95% CI, –0.2% to 1.4%) and the mean loss in the control group was –1.2% (95% CI, –2.1% to –0.4%). The change in baseline, body mass, and adjusted body mass change in BMC between the groups was significant (p = 0.005), whereas no changes occurred in the biochemical composition of the cartilage, as investigated by MRI. Balance, muscle force, and cardiorespiratory fitness improved significantly more (3% to 11%) in the exercise group than in the control group. Progressively implemented high‐impact training, which increased bone mass, did not affect the biochemical composition of cartilage and may be feasible in the prevention of osteoporosis and physical performance–related risk factors of falling in postmenopausal women. © 2014 American Society for Bone and Mineral Research.